The role of Th2 immune pathway modulation in the treatment of severe asthma and its phenotypes: Are we getting closer? - Levine, Stewart J. (2010)
New therapeutic approaches are needed for severe asthmatics who are refractory to standard therapy with high doses of inhaled corticosteroids plus long-acting β2-agonists. Current treatment guidelines for severe asthmatics from the National Asthma Education and Prevention Program recommend the addition of oral corticosteroids, which are associated with significant morbidity, and for those with allergic asthma, anti-IgE. Genetic and translational studies, as well as clinical trials, suggest that in a sub-group of patients the pathobiology of severe asthma is mediated by immune pathways driven by Th2-type CD4+ T cells which produce a characteristic repertoire of interleukins, including IL-4, IL-5 and IL-13. Therefore, biological modifiers of Th2-type interleukins, such as monoclonal antibodies, soluble receptors and receptor antagonists, represent a rational strategy for developing new treatment approaches, but will need to be targeted to selected individuals in whom the appropriate Th2 immune pathway is “active.” The benefits of immune modifier therapies targeting Th2-type cytokines, however, will need to be weighed against the toxicities associated with inhibition of key biological pathways, as well as the expense of future medications. Therefore, future clinical trials will need to clearly establish the efficacy and safety of biological modifiers of Th2 immune pathways before these approaches can enter routine clinical practice for the treatment of severe asthma.